What is the Social Value of Second-Generation Biofuels? - Hertel, Thomas W.; Steinbuks, Jevgenijs; Tyner, Wallace E. (World Bank Group, Washington, DC, 2015)
What is second-generation biofuel technology worth to global society? A dynamic, computable partial equilibrium model (called FABLE) is used to assess changes in global land use for crops, livestock, biofuels, forestry, and environmental services, as well as greenhouse gas emissions, with and without second-generation biofuels technology. The difference in the discounted stream of global valuations of land-based goods and services gives the value of second-generation technology to society. Under baseline conditions, this to amounts to $64.2 billion at today's population or an increase of roughly 0.3 percent in the valuation of the world's land resources. This gain arises despite the fact that, in the baseline scenario, the technology does not become commercially viable until 2035. Alternative scenarios considered include: diminished crop yield growth owing to adverse climate impacts, flat energy prices, low economic growth, and high population growth, as well as greenhouse gas regulation. The most important factor driving second-generation valuation is greenhouse gas regulation, which more than doubles the social value of this technology. Flat energy prices essentially eliminate the value of second-generation technology to society, and high population growth reduces its value because of the heightened competition for land for food production.